2018
DOI: 10.7454/proust.v1i1.21
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic Experiences, Depressive Symptoms, Anxiety Symptoms and Common Mental Health Risk Factors of Urban and Non-Urban Dwellers in Indonesia

Abstract: The prevalence of risk factors and symptoms of mental-health problems has been found to be higher in urban than non-urban areas. However, most studies are conducted in developed countries, and we are unsure whether a similar pattern can be observed in a developing country. In the present study, we compared rates of common mental health risk-factors and symptoms of psychosis, depression, and anxiety between urban and non-urban residents. A community sample of 844 participants completed an anonymous cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In terms of sociodemographic characteristics, we found that living in an urban area was positively associated with NA among adolescents and young adults. Consistent with this result, Jaya and Wulandari [ 31 ] reported that among the general population in Indonesia, participants living in urban areas exhibited higher levels of loneliness, depression, symptoms indicative of psychosis, and negative-self schema. The greater magnitudes of mental health concerns in urban areas compared with those in nonurban areas may be attributable to the differing population densities.…”
Section: Discussionmentioning
confidence: 53%
“…In terms of sociodemographic characteristics, we found that living in an urban area was positively associated with NA among adolescents and young adults. Consistent with this result, Jaya and Wulandari [ 31 ] reported that among the general population in Indonesia, participants living in urban areas exhibited higher levels of loneliness, depression, symptoms indicative of psychosis, and negative-self schema. The greater magnitudes of mental health concerns in urban areas compared with those in nonurban areas may be attributable to the differing population densities.…”
Section: Discussionmentioning
confidence: 53%
“…The BCSS [45] is a 24-item self-report measure in which participants rate agreement with 6 positive and 6 negative beliefs about themselves and other people from 0 (No) to 4 (Believe totally). The BCSS has been used successfully in Japan and Indonesia [46, 47].…”
Section: Methodsmentioning
confidence: 99%
“…P revious studies have linked living in urban areas and mental health problems. The risk and prevalence of some major mental disorders (e.g., anxiety, mood, and psychotic disorders) are higher in urban compared to rural areas (Jaya & Wulandari, 2018;Nepomuceno, Cardoso, Ximenes, Barros, & Leite, 2016;Peen, Schoevers, Beekman, & Dekker, 2010;Sharifi et al, 2015). Studies in China (Long et al, 2014), Germany (Jacobi et al, 2014), and Denmark (Pedersen & Mortensen, 2001) show similar findings for schizophrenia.…”
mentioning
confidence: 99%